Flavescence dorée-derived leaf yellowing in grapevine (Vitis vinifera l.) is associated to a general repression of isoprenoid biosynthetic pathways - Teixeira, António (2020)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fpls.2020.00896/full#supplementary-material